Estudo comparativo de métodos de orientação da cabeça para o planejamento virtual de cirurgias ortognáticas - Afonso, Felipe Alexander Caldas (2022)
INTRODUCTION The 3D computer simulation was a paradigm shift in treating dentofacial deformities. However, the best way to achieve the Neutral Head Position (NHP) is still controversial. There there are need to perform comparative studies between the available protocols to assess the degree of accuracy of the methods. This work aims to evaluate the degree of discrepancy between PNC methods in a virtual environment. METHODS Ten consecutively selected patients with dentofacial deformities were included in the analysis. Each patient underwent all the following neutral head position acquisition protocols: (A) The CASS Protocol Method; (B) The Charlotte Protocol Method; (C) The Universal Protocol Method. Cone-beam computed tomography (CBCT) with CR bite registration was requested, and impressions of both dental arches were taken for 3D scanning. Then, for preparing and positioning the composite skulls in the PNC, the Anatomic Aligner software (Houston Methodist Research Institute) was used, generating a total of 30 composite skulls since each virtual patient was submitted to 3 transfer protocols of PNC. The discrepancies were evaluated by superimposing the 3D craniofacial models using the Gateno-Xia cephalometric analysis, followed by linear and angular differences measurements. If within limits recommended in the literature as being excellent (angular differences less than 4°, and linear differences less than 2mm, and for the midline of the maxilla less than or equal to 1mm), the most significant linear deviation being 1.1mm, and orientation of 2.3°, and a maximum maxillary midline deviation of 1mm, considering all oriented cranial composites. Also, paired comparative analyzes between the PNC methods were carried out, following the following comparisons: Group A against Group B, Group A against Group C, and Group B against Group C. The authors did not observe deviations from the values recommended in the literature in all comparative pairs. Finally, ANOVA statistical analysis did not show any statistically significant difference. DISCUSSION The authors confirm the hypothesis that all the head orientation methods evaluated in this study do not present statistically significant differences (P>0.05) and consider that when the preparation and orientation of the skull-composite are carried out in a controlled environment and by specialized professionals and trained in the surgical area, all head orientation techniques can be helpful, accurate and valid for the desired result. This is because the PNC check is always based on facial analysis and clinical data collected by the surgeon. CONCLUSION This study showed no statistical difference in accuracy between all the protocols listed for comparison, and it proved to be of paramount importance to provide surgeons with a reflection on which technique would be most appropriate for the treatment of patients with dentofacial deformities. At its center, always consider the main aspects that facilitate the surgeon's day-to-day clinical: Simplicity of execution, less time spent, and familiarity with the technique.